Be Careful and Watch Yourselves: Public Health in Jewish Teachings - Turner, Akiva (Advances in Social Sciences Research Journal, 2019)
In this brief article, the author will focus on primary prevention as discussed in Jewish religious texts regarding halacha (Jewish law) and will briefly explore Jewish approaches to wellness and primary disease prevention. This exploration will demonstrate how Judaism views primary disease prevention. These views are consistent with medical and public health but are driven by a divine purpose.